Advanced study on dry eye in diabetics - Yi Cui (Guoji Yanke Zazhi, 2014)
Diabetes mellitus is a metabolic syndrome characterized by hyperglycemia, and is caused by complex interaction between genetic and environmental factors. Diabetes mellitus can lead to various ocular surface disorders, including dry eye, superficial punctuatekeratitis, corneal epithelial defects, and recurrent corneal erosion et al. This review focuses on the domestic and overseas research progress on dry eye in diabetics.